Kritik sosial terhadap Pernikahan Misyar dalam Film The Matchmaker: Analisis wacana kritis Norman Fairclough - Mutia, Farah (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the representation of social criticism against the practice of misyar marriage in the Arabic film The Matchmaker (2023) using Norman Fairclough’s Critical Discourse Analysis model. Fairclough’s three-dimensional approach (text analysis, discursive practice, and social practice) is applied to reveal how the film represents, produces, and criticizes a marriage practice considered to reinforce gender inequality and patriarchal hegemony in contemporary Saudi Arabian society. The results show that The Matchmaker reproduces and simultaneously criticizes patriarchal ideology through discursive strategies such as religious-euphemistic diction, visual symbols, and narratives that display contradictions between sharia legitimacy and injustice against women. This study concludes that the film functions as a medium of symbolic resistance to oppressive social structures, while opening a space for critical dialogue on morality and gender relations in the context of modern Arab culture.